(untitled) (Biuletyn Kryminologiczny, 2021)
Artykuł stanowi zwięzłe przedstawienie podstawowych problemów związanych ze stosowaniem art. 37b k.k. Oparty jest na krytycznej analizie w stosunku do używania terminu „kara mieszana” oraz zakresu poszczególnych składników tejże sankcji. Zawiera rozważania co do możliwości równoczesnego orzekania kumulatywnej kary grzywny, terminów biegu przedawnienia oraz zatarcia skazania. The article presents basic problems of the institution of accumulative penalty, which was introduced in the Act of 20 February 2015 in Art. 37b Criminal Code. It is based on the critical analysis about using term “mixed penalty” and about purview all of components of this penalty. The article includes consideration about: ability of adjudicating fine in tandem with Art. 37b C.C, prescription and expungement conviction.